2020
DOI: 10.3390/fire3020013
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Propensities of Old Growth, Mature and Regrowth Wet Eucalypt Forest, and Eucalyptus nitens Plantation, to Burn During Wildfire and Suffer Fire-Induced Crown Death

Abstract: There are conflicting conclusions on how the flammability of wet eucalypt forests changes in the time after disturbances such as logging or wildfire. Some conclude that forests are most flammable in the decades following disturbance, while others conclude that disturbance has no effect on flammability. The comparative flammability of Eucalyptus nitens plantations in the same environment as wet eucalypt forest is not known. We determined fire incidence and fire severity in regrowth, mature and old growth wet eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Similar kinds of interactions between stand age and forest flammability have been found in other parts of the world (e.g. Tiribelli, Morales, Gowda, Mermoz, & Kitzberger, 2018; Winoto‐Lewin, Sanger, & Kirkpatrick, 2020; Zald & Dunn, 2017; Zylstra, 2018). Several factors likely contribute to these stand age–flammability relationships.…”
Section: Examples Of Interactions Among Disturbances In Mountain Ash supporting
confidence: 67%
“…Similar kinds of interactions between stand age and forest flammability have been found in other parts of the world (e.g. Tiribelli, Morales, Gowda, Mermoz, & Kitzberger, 2018; Winoto‐Lewin, Sanger, & Kirkpatrick, 2020; Zald & Dunn, 2017; Zylstra, 2018). Several factors likely contribute to these stand age–flammability relationships.…”
Section: Examples Of Interactions Among Disturbances In Mountain Ash supporting
confidence: 67%
“…However, evidence presented in (Attiwill et al 2014) actually showed that crown fires had occurred twice as frequently in regrowth when compared to old growth forests. Similarly, (Price and Bradstock 2012) and (Winoto-Lewin et al 2020) also found that the likelihood of crown fire declined in ash-type forests as they age. Attiwill et al (2014) have elected to ignore the broader body of evidence on relationships between logging and fire, including data in their own study.…”
Section: Before the Fire -Logging Makes Forests More Prone To High Sementioning
confidence: 79%
“…A series of studies has shown that the severity of wildfires is influenced by the condition of the forest at the time of the fire (Bradstock and Price 2014;Lindenmayer et al 2009;Taylor et al 2014;Tiribelli et al 2018;Winoto-Lewin et al 2020;Zylstra 2009;Zylstra 2018) . A detailed empirical study after the 2009 Black Saturday wildfires in Victoria showed that logged in wet eucalypt forests that had been regenerated after harvesting were at seven times greater risk of burning at high severity than older, unlogged forests (Taylor et al 2014).…”
Section: Before the Fire -Logging Makes Forests More Prone To High Sementioning
confidence: 99%
See 2 more Smart Citations